Annealing effect on the optical properties and interdiffusion of MgO/Zr/MgO multilayered selective solar absorber coatings. (October 2015) - Nuru, Z.Y.; Perez, D.; Kaviyarasu, K.; Vantomme, A.; Maaza, M.
Highlights: MgO/Zr/MgO solar absorber was heated in air at different temperatures. MgO/Zr/MgO solar absorber was thermally stable up to 300 °C for 2 h. RBS analysis was used to study interdiffusion between the layers. At 400 °C, interlayers between MgO & Zr layers, and oxidation of Zr was found. The coatings were thermally stable in air up to 250 °C for 24 h. Abstract: Selective solar absorber coatings based on MgO/Zr/MgO multilayered coatings were prepared onto Zr coated stainless steel substrates using e-beam evaporation. It was found that MgO/Zr/MgO multilayered solar absorber coatings exhibited a good spectral selectivity of 0.91/0.12. The effect of annealing on the optical properties and interdiffusion between the layers was investigated. Annealing the multilayered coating in air up to 300 °C did not show significant change on the spectral selectivity as well as on the interdiffusion between the layers indicating the coating's thermal stability up to that temperature. Annealing in air at 400 °C leads to decrease in solar absorptance and an increase in thermal emittance considerably, which was due to the interlayers appeared between MgO and Zr layers, oxidation of Zr layers, and change in both thickness and composition of the layers as investigated by RBS analysis. The MgO/Zr/MgO MSSACs were found to be thermally stable up to 250 °C in air for 24 h.